Satisfaction with the neighborhood environment and health in older elderly: cross-sectional evidence from the Bambuí cohort study of aging - Tatiana Chama Borges Luz; Cibele Comini César; Maria Fernanda Lima-Costa; Fernando Augusto Proietti
In order to investigate the association between satisfaction with the neighborhood environment and self-rated health among older elderly, data from 814 participants of the eleventh wave of the Bambuí Cohort Study of Aging were analyzed using robust Poisson regression analyses. Those elderly with higher satisfaction with their neighborhoods (PR = 0.75; 95%CI: 0.63-0.87) were less likely to report worse self-rated health. The number of chronic diseases (two, PR = 1.69; 95%CI: 1.05-2.70, three or more, PR = 1.99, 95%CI: 1.27-3.13), difficulty in performing daily activities (PR = 1.51; 95%CI: 1.28-1.78), presence of depressive symptoms (PR = 1.68; 95%CI: 1.44-1.95) and frequency of leisure-time exercise in previous 90 days (less than once a week, PR =1.24; 95%CI: 1.03-1.50) were all positively and significantly associated with poor self-rated health. This study provided empirical evidence that satisfaction with the neighborhood environment was associated with the health of the older elderly. The findings further suggest the potential importance of including this indicator in analyses of place and health among the elderly.